Photothermal catalysis of waste plastics into propionic acid and hydrogen via Ni single-atom site isolation effect - Shuai Yue; Yixiao Liu; Zhiyong Zhao; Guanshu Zhao; Mengxue Yang; Tao Zhang; Fei Li; Kewang Liu; Pengfei Wang; Sihui Zhan; Jinhu Jia (Proceedings of the National Academy of Sciences, 2025)
Currently, catalytic recycling of polyethylene (PE) into high-value chemicals using solar energy often faces poor product selectivity and low efficiency. This is mainly due to the difficulty in effectively controlling the intermediates during PE photoreforming and the long-standing challenge of inefficient charge dynamics. Here, we present a solar-driven photothermal catalytic approach for the selective conversion of PE waste into propionic acid and hydrogen under ambient conditions. Atomically dispersed Ni sites supported on CeO 2 (Ni SA /CeO 2 ) achieve a propionic acid yield of 331 μmol h –1 with 94.8% selectivity in the photothermal reaction. This performance is 1.6 times higher than that of catalysts supported by Ni clusters (Ni NP /CeO 2 ). Additionally, Ni SA /CeO 2 exhibits a hydrogen yield of 0.23 mmol h –1 with stable long-term performance. Mechanistic studies reveal that single Ni atoms form linear coordination with oxygen atoms in CeO 2 , introducing unoccupied mid-gap states that effectively capture hot electrons and enhance the photothermal effect through local hotspot formation. In contrast, Ni clusters suffer from inefficient heat accumulation due to multistep phonon scattering. Furthermore, site isolation of Ni single atoms spatially separates the reaction intermediates and suppresses dimerization of the key intermediate COOHCH 2 CH 2 *, thereby greatly improving the selectivity for propionic acid. In contrast, closely packed Ni cluster sites promote intermediate coupling and the formation of undesirable byproducts, reducing selectivity. This work provides mechanistic insights into the advantages of atomic-scale catalyst design for selective chemical transformations.